Piety and Politics:: Islamism in Contemporary Malaysia by Joseph Chinyong Liow (New York: Oxford University Press, 2009. hbk. 282 pages) (American Journal of Islam and Society, 2011)
For much of the twentieth century, race and ethnicity formed the basis ofMalaysian politics and, therefore, dominated its discourse. This book exploreshow over the past thirty years the politics of Malaysia, which wasonly approximately 60 percent Muslim, moved strongly in an Islamist direction,indeed, “how Islam—in particular its ideological and institutionalexpressions—informs the configuration of power, the nature of legitimacy,and the sources of authority in Malaysian politics and society today” (xii).To do so, Liow first examines the genesis of the Islamist agenda from theperspective of the two major political parties—the Islamist oppositionParti Islam se-Malaysia (PAS) and the dominant United Malay NationalOrganisation (UMNO)—showing how the latter went through severalchanges as it evolved to place Islamism at the center of its sociopoliticalagenda. He then proceeds to show how the UMNO-led government of Malaysia began to create institutions of Islamic governance, a process heterms the “bureaucratization” of Islam, which formed the basis for PrimeMinister Mahathir’s claim in the 1990s that Malaysia, constitutionally asecular state, was an Islamic state. As he does so, he notes the tensions thatthese developments caused between the federal and state administration onthe one hand and civil and religious law on the other. Liow moves on toexplore the debate from the 1990s between PAS and UMNO, and withinPAS itself, on how Islam might be expressed as the organizing principlefor society and politics in a religiously plural Malaysia and how the non-Muslim communities responded to the parties’ endeavors ...